MENAPAKI ERA REVOLUSI INDUSTRI 4.0 : PELUANG ATAU TANTANGAN BAGI PUSTAKAWAN? - Nur Sanny Rahmawati (Perpustakaan Nasional RI, 2020)
The presence of the Industrial Revolution 4.0 has been increasing the ease and speed for people in accessing information. However, the presence of it also raised the skepticism of the libraries and librarians’ existence, as agents of information and knowledge dissemination. The purpose of this study is to find out whether the Industrial Revolution 4.0 is an opportunity or challenge for librarians. The approach used in this study is qualitative method and literature review. The results of this study is that in the era of the Industrial Revolution 4.0, both information validation, digital literacy, and ICT capabilities are challenges and opportunities for librarians. This can also be overcome by librarians constantly increasing their competence, both basic, core, and specifically, broadening the focus of services, proactive towards what users’ needs, utilizing digital infrastructure to enhance library awareness and the existence of the library, participate in the library studies research, creating user-based activities experience, actively build networks between librarians and also in professional organizations, as well as being sensitive to the issue of librarianship globally.